Penguatan Mental dan Spiritual Petugas Haji - Qodariah Barkah (CV. Doki Course and Training, 2024)
This service aims to provide strong mental and spiritual preparation for the hajj officers. This is because both officers and pilgrims often experience stress, anxiety disorders and depression. This service is carried out using a counseling method. This service activity was carried out at the Palembang Hajj Dormitory with participants from the hajj officers of the South Sumatra Province. This service activity has been carried out well. The results show an increase in understanding and mental readiness of the participants, preventing hajj officers from stress, anxiety disorders and depression so that they are expected to be able to provide more effective services to the congregation and can motivate the congregation to carry out the hajj pilgrimage sincerely only because of Allah.